Pengelolaan Merdeka Belajar dan Kampus Merdeka - Nelfia Nofitri; Ilmi, Darul (STAI Darul Quran Payakumbuh, 2023)
The rapid development of science and technology has brought many changes in various aspects of life. This of course requires people to be able to adapt to the times. To answer the challenges of that era, it was necessary to have the presence of the Independent Learning Independent Campus (MBKM) to create a new paradigm in the world of education, including higher education. The Minister of Education and Culture's 2020 policy with the MBKM concept is considered relevant and appropriate to implement in the current democratic era. According to Nadiem Makarim, the basic concept of choosing independent learning is because it was inspired by the philosophy of K.H. Dewantara with an emphasis on independence and independence. MBKM consists of two essential concepts, namely